Computerised cognitive assessment of concussed Australian Rules footballers. Issue 5 (1st October 2001) - Makdissi, M; Collie, A; Maruff, P; Darby, D G; Bush, A; McCrory, P; Bennell, K
Abstract : Background —"Paper and pencil" neuropsychological tests play an important role in the management of sports related concussions. They provide objective information on the athlete's cognitive function and thus facilitate decisions on safe return to sport. It has been proposed that computerised cognitive tests have many advantages over such conventional tests, but their role in this domain is yet to be established. Objectives —To measure cognitive impairment after concussion in a case series of concussed Australian Rules footballers, using both computerised and paper and pencil neuropsychological tests. To investigate the role of computerised cognitive tests in the assessment and follow up of sports related concussions. Methods —Baseline measures on the Digit Symbol Substitution Test (DSST), Trail Making Test-Part B (TMT), and a simple reaction time (SRT) test from a computerised cognitive test battery (CogState) were obtained in 240 players. Tests were repeated in players who had sustained a concussive injury. A group of non-injured players were used as matched controls. Results —Six concussions were observed over a period of nine weeks. At the follow up, DSST and TMT scores did not significantly differ from baseline scores in both control and concussed groups. However, analysis of the SRT data showed an increase in response variability and latency after concussion in the injured athletes. This was in contrast with a decrease in response variability and no change in latency on follow up of the control players (p<0.02). Conclusion —Increased variability in response time may be an important cognitive deficit after concussion. This has implications for consistency of an athlete's performance after injury, as well as for tests used in clinical assessment and follow up of head injuries.